تطور الوضع السياسي والعسكري في عهد البيلربايات بالجزائر - شوقي, عبد الكريم (جامعة الوادي - University of Eloued, 2022)
مواصلة للنتائج الجد إيجابية التي حققتها الجزائر خلال فترت عهد البايلرباي خير الدين، الذي استمر من عام 1519م تاريخ توليه قيادة البلاد تحت راية الخلافة العثمانية، إلى عام 1546م تاريخ وفاته بإسطنبول، فان خلفائه من البايلربايات الذي تعاقبوا على قيادة الجزائر، استمروا على نفس السياسة التي وضعها سابقهم، الذي كان قد سعى إلى ربط الجزائر بالخلافة العثمانية، وتأسيس نمط جديد للدولة الجزائرية وهيكلتها، يصعب تغييره بسرعة، كما كان له تأثير كبير في تطور الأحداث بالمنطقة، لذلك فإن تطور نمط الحكم لم يتغير كثيرا، وبقي مرتبطا بشخصية الحاكم ومدى اهتمامه بذلك الجانب. ولمحاولة الوقوف عند حقيقة تطور الوضع السياسي والعسكري في تلك الفترة بالجزائر من جهة، وفي المجال الذي كان يحيط بها من جهة أخرى، سوف يتم التعرض لمختلف جوانبه، وأهم أحداثه وعملياته، من خلال هذا المقال، في محاولة للإحاطة قدر الإمكان بالموضوع، عن طريق استعراض أهم التطورات التي عرفها، وكذا مختلف الصفحات التي طواها. Going on the very positive results achieved by Algeria during the period of the reign of Bailirbay Khair al-Din, which lasted from 1519, the date of his assumption of the leadership of the country under the banner of the Ottoman Caliphate, to 1546, the date of his death in Istanbul, His successors from the Bailirbays who succeeded in leading Algeria, continued the same policy set by their predecessor, who had sought to link Algeria to the Ottoman Caliphate, and to establish a new pattern for the Algerian state and its structure, which is difficult to change quickly, as it had a significant impact on the development of events in the region, therefore, the evolution of the pattern of governance did not change much, and remained linked to the personality of the ruler and the extent of his interest in that aspect. And to try to stand at the reality of the development of the political and military situation in that period in Algeria on one hand, and in the field that surrounded it on the other hand, it will be exposed through this article to its various aspects, its most important events and operations, in an attempt to be as brief as possible on the subject, by reviewing the most important developments witnessed, as well as the various stages passed.
مقال
Keywords: الجزائر ; الاسبان ; حسن بن خير الدين ; صالح رايس ; العلج علي ; وهران ; الكونت دالكوديت; Algeria; the Spaniards; Hassan bin Khair al-Din; Saleh Rais; Alj Ali; Oran; Count Dalcodet